Peran Corporate Image Dalam Memediasi Pengaruh Corporate Social Responsibility Terhadap Purchase Intention Air Minum Dalam Kemasan Merek Ades Di Kota Denpasar - Premayani, Ni Wayan Wina; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen, 2015)
This study aims to examine the role of the corporate image in mediating the effect of corporate social responsibility to the purchase intention of bottled water brand ades. This research was conducted in the city of Denpasar. Method of determining the sample in this study was non-probability sampling with purposive sampling technique, namely the determination of the sample with particular consideration. Data collected using a questionnaire with Likert scale. Respondents in this study were 100 respondents. Data analysis techniques used in this research is the analysis of pathways. These results indicate that Corporate Social Responsibility has a positive and significant impact on the Corporate Image products bottled water brand Ades, Corporate Social Responsibility has a positive and significant impact on Purchase Intention bottled drinking water products brand Ades, Corporate Image has a positive and significant impact Intention to Purchase bottled water products brand Ades. Corporate Image significantly mediate the indirect influence of corporate social responsibility to the purchase intention of bottled water products brand Ades.
Keywords: corporate social responsibility; corporate image; purchase intention